Effect of concurrent use of anti‐retroviral therapy and levonorgestrel sub‐dermal implant for contraception on CD4 counts: a prospective cohort study in Kenya. Issue 1 (1st March 2013) - Hubacher, David; Liku, Jennifer; Kiarie, James; Rakwar, Joel; Muiruri, Peter; Omwenga, Jackline; Chen, Pai‐Lien
Abstract : Introduction: Simultaneous use of contraceptive hormones and anti‐retroviral therapy (ART) may theoretically lessen the effectiveness of both. Women on ART need assurance that hormonal contraception is safe and effective. The sub‐dermal implant is an ideal product to study: low and steady progestin release and no adherence uncertainties. We sought to determine if the medications' effectiveness is compromised. Methods: We conducted a prospective cohort study among women on first line ART (stavudine or zidovudine and lamivudine+nevirapine). We recruited new implant users and matched them to women not using hormonal contraception, based on age and baseline CD4. Participants were followed prospectively for up to two years, recording serial CD4 measures and medical histories. We used generalized growth curve models and Wald chi‐square tests to compare changes in CD4 counts across study groups. Prospective CD4 measures were censored (excluded) if any of the following events occurred: change in ART, implant removal or use of any hormonal contraception among controls. We examined incidence of opportunistic infection and pregnancy. Results: We matched 48 implant users to 33 non‐hormonal controls. Over time, CD4 counts for both groups rose slightly but did not deviate significantly from each other ( p =0.44). Opportunistic infection rates did not differ between the groups. None of the implant users and one of the non‐hormonal controls became pregnant during follow‐up. Conclusions: This small study found concurrent use of contraceptive implants and ART to be safe and effective. Although other hormonal contraceptive products and ART regimens may interact in unknown ways, the results of this study are reassuring.